Mediating Role of Resilience and its Impact on Psychological Well-Being, and Mental Distress among Mental health Nurses - Abdalhadi Hasan PhD; Amal Alsulami PhD (SAGE Open Nursing, 2024)
Introduction Mental health nurses (MHNs) are categorized as demanding specialists with high levels of stress, and their career is recognized as a high-risk career Objective The study aims to assess the relationships between psychological well-being (PWB), mental distress, and resilience among MHNs. Also, it aims to identify the significant predictors of the psychologic well-being of MHNs. Methods The study utilized a cross-sectional survey design with a random sample of 250 MHNs who were requested to complete DASS 21, Ryff's scale of PWB and Connor Davidson's resilience scale. Results The results revealed that two-thirds of nurses reported either a severe or extreme level of stress (n = 166, 66%), and more than half experienced a severe to extreme level of anxiety (n = 140, 56%). Approximately 25% of MHNs reported a severe to extreme level of depression (n = 62, 25%). The results also indicated that there is a statistically significant negative relationship between PWB subscales and DASS 21. The results indicate that the depression subscale is significantly varied based on the demographic characteristics of nurses. Similarly, this is the case for the anxiety and stress subscales. Conclusion The study showed that MHNs’ resilience intervenes with perceived mental distress. Enhancing MHNs resilience would improve PWB and mental health. The study results conclude that MHNs with a high level of resilience reported lower mental distress and a better working environment. Thus, MHNs should be introduced to crisis intervention in order to improve resilience levels.